Building new kinds of meta-models to analyse experimentally (companion) modelling processes in the field of natural resource management. (October 2019) - Bonté, Bruno; Farolfi, Stefano; Ferrand, Nils; Abrami, Géraldine; Diallo, Mamadou Ciss; Dubois, Dimitri; Johannet, Anne; Gaudi, Wanda Aquae
Abstract: In order to better manage complex situations of natural resource management, models are built in a participative way, involving the stakeholders of these situations in participatory modelling activities. The impact that this activity of participatory modelling has on the stakeholders is at the heart of the Companion Modelling approach but this impact is hardly possible to evaluate on the field. In this paper we propose a general framework to study in vitro the impact of participatory modelling on natural resources management. We illustrate our framework by proposing an experimental setting that looks at participatory modelling in the context of water management. We realized a pilot experiment and show that this experimental setting can be used to test, in the laboratory, the hypothesis that participatory modelling of a common pool resource situation has an impact on the way the resource is managed and increases the cooperative behaviour of stakeholders. Highlights: A conceptual framework to design reflexive studies on the modelling of Social and Ecological Systems. A study that combines meta-modelling and experimental economics. An experimental design that instantiates the conceptual framework. An associated software system based on NetLogo has been implemented and tested and is provided with its documentation.